Pengaruh Environmental Knowledge Terhadap Green Consumption Behavior dengan Environmental Awareness Sebagai Variabel Intervening Pada Generasi Milenial Kota Padang - Widiastuti, Herlina; Cerya, Efni (Universitas Batanghari Jambi, 2026)
This study analyzes the influence of environmental knowledge on green consumption behavior, with environmental awareness as an intervening variable, among the millennial generation in Padang. The increasing importance of environmental issues and unsustainable consumption habits make knowledge and environmental awareness strategic factors in the development of green consumption behavior. This study uses a quantitative approach with path analysis to examine the direct and indirect relationships between these variables. The sample consists of 400 respondents who were selected through multistage random sampling to determine the region and then selected through purposive sampling. The data were collected using questionnaires and processed using SPSS Version 25. The results of the study show that environmental knowledge has a positive and significant influence on green consumption behavior. Furthermore, environmental awareness reinforces this influence as an intervening variable. These results confirm that improving environmental knowledge in combination with high environmental awareness contributes optimally to promoting environmentally friendly consumption behavior.